Comparison between Insulin-like Growth Factor Binding Protein-1 Level and Bishop Score as Predictor of Successful Labor Induction in Full Term Pregnancy with Preeclampsia - Setiyorini, Nurul; Cahyanti, Ratnasari Dwi (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2020)
Introduction: preeclampsia/eclampsia contributed to 30% of maternal mortality in RSUP Dr. Kariadi. Pre-induction bishop score assessment is a standard for cervical maturity estimation. Other predictors currently being developed, including insulin-like growth factor binding protein-1 (IGFBP-1). However, there is no cut-off point for IGFBP-1 examination in full term pregnancy, especially with preeclampsia and its complications. Objective: to find IGFBP-1 levels and Bishop Score differences in preeclampsia women with induction labor.Methods: this prospective observational cohort study was conducted in preeclampsia women with gestational age ≥37 weeks planned labor induction at Obstetrics and Gynecology Ward RSUP Dr. Kariadi Semarang and networking hospital during study period (n=66). History taking, physical examination, proteinuria, cervical mucus IGFBP-1, and bishop score calculation was performed. Statistical analysis was performed with paired-t test, followed by ROC for cut-off value of successful induction prediction, and logistic regression to determine confounding variables effect on IGFBP-1 levels.Results: The average Bishop score of 66 subjects was 2.5±1.81 and 2.6±1.8 for women who deliver ≤24 labor and in labor for ≤12 hours, respectively. Although the bishop score was higher in the successful labor group, there was no significant difference between groups. Mean IGFBP-1 value was 8.29±5.033 mcg/L with median value of 10.8 mcg/L. Successful induction had significant higher IGFBP-1 levels with area-under-curve (AUC) 0.76 and 8.145 cutoff value (p=0.002, RR=5.1).Conclusion: IGFBP-1 level with cutoff point 8.145 can be used as predictor of successful labor induction in term pregnancy with preeclampsia.